Optomyelitis associated with the presence of antibodies to myelin oligodendrocyte glycoprotein. Case report - Kalashnikova, Anastasiia K.; Sheremet, Nataliia L.; Andreeva, Natalia A.; Zhorzholadze, Nino V.; Ronzina, Irina A.; Kaloshina, Anna A. (Consilium medicum (Online), 2022)
Antibodies to myelin-oligodendrocyte glycoprotein (anti-MOG-IgG) is a specific biomarker that has been detected in peripheral blood from children with acute multiple encephalomyelitis (ADEM) as well as in adults with aquaporin-4 (AQP4), associated with seronegative opticoneuromyelitis spectrum disease (NMOSD), brainstem encephalitis, longitudinally disseminated transverse myelitis, and optic neuritis. Most experts now consider MOG-IgG-associated disorder (MOG-AD) an independent disease immunopathogenetically distinct from classical multiple sclerosis (MS) and aquaporin-4 (AQP4)-IgG-positive optomyelitis. Isolated, bilateral, and less frequently unilateral OH, with simultaneous or sequential involvement of the eyes, is the most frequent clinical manifestation of MOG-AD. Because of the significant overlap in the clinical and radiological picture, MOG-AD is often misdiagnosed as MS. Timely diagnosis is critical to ensure appropriate treatment. This article describes a clinical case of anti-MOG-IgG encephalomyelitis with late-onset ON initially diagnosed as MS.